A Micro Level Perspective of Euroization in Albania - Edlira Narazani (The Vienna Institute for International Economic Studies (wiiw), 2013)
This research investigates what drives the euroization in Albania. By using survey data collected in one of the main Albanian cities, we find that factors like remittances, financial literacy, perception of high inflation and trust in financial system play an important role in the extent of euroization together with the experience of past events. Factors related to the future, such as the expectation on the exchange rate fluctuations, seem to not be correlated with the extent of euroization. As regards the current Eurozone crisis, its impact on euroization results to be mediated by the (mis)trust in EURO rather than local currency.
Keywords: E41; E50; D14; C83; 330; Euroization; currency substitution; survey data; eurozone crisis